Analysis of Students’ Problems Related to Learning Discipline at MTs Masmur - Risma, Nova; Anugrah, Fezyana Delsa; Henjilito, Raffly (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Learning discipline is an important aspect in supporting the success of student learning. This article aims to describe the problems of student learning discipline at MTs Masmur. The method used is a literature study with a descriptive approach through a review of relevant scientific literature. The results of the study show that learning discipline problems include tardiness, lack of compliance with rules, low motivation to learn, and lack of responsibility in completing assignments. Therefore, cooperation between teachers, schools, and parents is needed to instill the values of learning discipline.